2017
DOI: 10.1353/hpu.2017.0014
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Barriers and Facilitators to Health Care Utilization in the United States for Transgender People: A Review of Recent Literature

Abstract: Transgender people face numerous barriers when utilizing health care in the United States. The current study sought to highlight transgender consumer perspectives in order to present theoretically informed, concrete recommendations for increasing transgender health care utilization. The search yielded several prominent themes associated with barriers to health care for transgender people: 1) provider lack of knowledge concerning transgender identity issues and transgender health issues, 2) transgender patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
98
1
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(111 citation statements)
references
References 45 publications
9
98
1
3
Order By: Relevance
“…Basic requirements, including feeling safe and validated, are not being met. Consistent with previous research [5,[7][8][9][10][11], transgender participants in this study frequently indicated that current knowledge, experience, and professionalism amongst healthcare professionals around transgender health is poor and that there is a pressing need for better training for health professionals and more research in transgender healthcare. This includes training regarding using the correct name and pronouns, which has been shown to be vitally important in validating TGD experiences [10,[12][13][14].…”
Section: Discussionsupporting
confidence: 86%
“…Basic requirements, including feeling safe and validated, are not being met. Consistent with previous research [5,[7][8][9][10][11], transgender participants in this study frequently indicated that current knowledge, experience, and professionalism amongst healthcare professionals around transgender health is poor and that there is a pressing need for better training for health professionals and more research in transgender healthcare. This includes training regarding using the correct name and pronouns, which has been shown to be vitally important in validating TGD experiences [10,[12][13][14].…”
Section: Discussionsupporting
confidence: 86%
“…This research employs the unique approach of having youth comment on themes from healthcare providers, which yields strong recommendations that are directly relevant to the work force and their training needs. In this way, this study builds on previous research from both youth and adults (Corliss et al, 2007;Lerner & Robles, 2017;Roberts & Fantz, 2014;Safer et al, 2016;Snyder et al, 2016;Stoddard et al, 2011) regarding experiences of discrimination and other barriers to healthcare. Intervention and training activities based on these findings will address shortcomings in existing healthcare provider education and the expressed need for more robust training on…”
Section: Theme 2: Training For Healthcare Providersmentioning
confidence: 98%
“…Research has identified discrimination and a lack of knowledgeable healthcare providers as major barriers for TGD individuals seeking care (Corliss, Belzer, Forbes, & Wilson, 2007;Lerner & Robles, 2017;Roberts & Fantz, 2014;Safer et al, 2016;Snyder, Burack, & Petrova, 2016;Stoddard, Leibowitz, Ton, & Snowdon, 2011). Ignorance of gender issues may lead to unintentional but nonetheless stigmatising slights; examples of discriminatory mistreatment range from misuse of names and pronouns to outright denial of care for transgender patients (Grant et al, 2011).…”
mentioning
confidence: 99%
“…We examine the healthcare system and the labor market as two gendered institutions that influence BMSM’s preventive healthcare practices (Dovel et al, 2015; Fleming & Dworkin, 2016) and show how BMSM are negatively impacted by heteronormatively gendered institutional processes in health care and labor market settings. Assumptions about gender as a binary category mean that men often pay a penalty—in the form of social exclusion and stigma—for being gender non-conforming (Frye et al, 2015; Lerner & Robles, 2017; Messner, 1997; Sabo, 2005; Sevelius, Deutsch, & Grant, 2016). …”
Section: Introductionmentioning
confidence: 99%